Development of high-temperature heavy density dolerite concrete for 4th generation nuclear power plants - Khan, Muhammad Nasir Ayaz; Malik, Azhar Hussain; Yaqub, Muhammad; Umar, Muhammad; Noman, Muhammad; Abid, Muhammad; Alabduljabbar, Hisham; Mohamed, Abdullah; Zaidi, Syed Salman Ahmad (Frontiers in Materials, 2023)
This study examines the physical, mechanical, microstructural, and attenuation properties of high-density concrete exposed to temperatures ranging from 200°C to 1200°C. For this purpose, heavy-density concrete containing 25%, 50%, 75%, and 100% dolerite aggregates was developed and compared with three ordinary concrete mixes. Pre- and post-heated concrete specimens were evaluated for mass and density loss, compressive strength, rebound hammer, X-ray and gamma-ray attenuation, Half Value Layer (HVL), and Ten Value Layer (TVL) along with microstructural properties determined by scanning electron microscopy and Energy Dispersive X-ray. The results showed that the incorporation of 75% dolerite aggregate during pre- and post-heating yielded high compressive strength whereas low mass and density loss. The same mixture showed significant improvement in gamma ray shielding at all temperatures. The Half Value Layer and Ten Value Layer values showed a reduction in the thickness of concrete as a shield. It is recommended that dolerite heavy-density concrete is a potential radiation shield at high temperatures ranging from 200°C–1200°C in fourth-generation nuclear power plants.